Examination of the effects of a new compression garment on skin tissue oxygenation in healthy volunteers. (2nd July 2019) - Chohan, Ambreen; Haworth, Lauren; Sumner, Simon; Olivier, Mairi; Birdsall, Daniel; Whitaker, Justine
Abstract : Objective: Compression devices have been shown to reduce venous stasis, increase blood flow and skin tissue oxygenation (StO2 ), promoting healthy tissue. This study aimed to explore the efficacy of a new compression garment in three different positions in healthy adults. Methods: In this quantitative study, potential participants were screened and recruited using the Physical Activity Readiness Questionnaire (PAR-Q, Canada). Participants attended three separate, one-hour sessions to evaluate StO2 in supine-lying, chair-sitting and long-sitting positions. StO2 was recorded for 20 minutes pre-, during and post- a 20-minute intervention using a compression garment, TributeWrap (Lohmann-Rauscher, Germany). A repeated-measures analysis of variance (ANOVA) was followed by post-hoc pairwise comparisons. Results: A total of 28 healthy volunteers took part (aged 24.6 ±8.4years; 13 males, 15 females). A significant difference was seen between the three positions (p<0.001). Chair-sitting had the lowest StO2 pre-intervention, increasing StO2 significantly (32.25%, p<0.001) during wear of the compression garment (24.8% higher than baseline post-intervention). No significant difference was seen between long sitting and supine-lying (p=1.000). In contrast, long-sitting and supine-lying StO2 was higher pre-intervention compared with chair-sitting and only increased post-intervention (11% and 16.8% respectively, p<0.001) compared with baseline. Conclusion: The compression garment significantly increased StO2 levels in both seating positions. Further studies are required to determine if increasing StO2 through short intervention sessions with this device has the potential to improve self-management of tissue health in individuals with reduced mobility, oedema or venous insufficiency.